Підготовка фахівців для професійної діяльності за допомогою комп’ютерних і комунікаційних технологій - Кучай Тетяна; Kucsáj Tetjána; Kuchai Tetiana; Кучай Олександр; Kucsáj Olekszandr; Kuchai Oleksandr („RIK-U” Kft., 2019)
Анотація. Розглянуто проблему інформатизації суспільства, яка є однією з актуальних проблем науки і практики людського існування. Інформатизація і потужне технічне оснащення суттєво сприяють гуманітаризації освіти і гуманізації навчального процесу. Перед системою вищої професійної освіти постало завдання підготовки фахівців високого ґатунку, творчих особистостей, які б відповідали інтересам та запитам учнів і водночас потребам суспільства. Інформатизація системи освіти як одна з ланок загального процесу професійної підготовки фахівця має на меті підвищення ефективності навчання завдяки розширенню обсягів інформації та вдосконаленню методів її застосування.

Abstract. The problem of informatization of society is considered, which is one of the vital problems of science and practice of human existence. Informatization and powerful technical equipment make a significant contribution to the humanization of education and the humanization of the educational process. The system of higher professional education faces the challenge of training high-level specialists, creative personalities that respond to the interests and demands of students and, at the same time, the needs of society. Informatization of the education system as one of the parts of the general process of vocational training of a specialist, aims at increasing the effectiveness of learning through the expansion of the volume of information and improving its methods of application.
Ikt-technológiák alkalmazása a szakmai tevékenységre való felkészítésben
Preparing specialists for professional work by means of computer and communication technologies
https://kmf.uz.ua/wp-content/uploads/2019/04/Final-Pedagogical_conf_2019_03_28-29.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00007073
Keywords: підготовка фахівця; інформатизація суспільства; система освіти